CHEMICAL AND DYNAMICAL EVOLUTION IN THE SOLAR NEIGHBOURHOOD - Bienaym’e, O.; Mishenina, T.; Kovtyukh, V.; Soubiran, C. (Одеські астрономічні публікації, 2017)
We measure the surface mass density of the galactic disk in the solar neighbourhood using two samples of red clump stars, we also determine the thin and thick disk chemical properties. High resolution spectral data of red clump stars towards the NGP have been obtained with the spectrograph Elodie at OHP for Tycho-2 selected stars. Nearby Hipparcos red clump stars were also observed with the Elodie spectrograph.